2007
DOI: 10.1379/csc-255.1
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the αB-crystallin domain responsible for inhibiting tubulin aggregation

Abstract: The cytoskeleton has a unique property such that changes of conformation result in polymerization into a filamentous form. ␣B-Crystallin, a small heat shock protein (sHsp), has chaperone activities for various substrates, including proteins constituting the cytoskeleton, such as actin; intermediate filament; and tubulin. However, it is not clear whether the ''␣-crystallin domain'' common to sHsps also has chaperone activity for the protein cytoskeleton. To investigate the possibility that the C-terminal ␣-crys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 25 publications
2
23
0
Order By: Relevance
“…Chaperone proteins possess the ability to prevent target protein interactions and aggregation of misfolded proteins 14 ; they are, thereby, protective molecules during times of stress or shock. The domain of α-B-crystallin inhibits the aggregation of tubulin and other microtubuleassociated proteins in particular [15][16][17] . Decreased α-B-crystallin occurs with muscular atrophy and is associated with decreased amounts of tubulin 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Chaperone proteins possess the ability to prevent target protein interactions and aggregation of misfolded proteins 14 ; they are, thereby, protective molecules during times of stress or shock. The domain of α-B-crystallin inhibits the aggregation of tubulin and other microtubuleassociated proteins in particular [15][16][17] . Decreased α-B-crystallin occurs with muscular atrophy and is associated with decreased amounts of tubulin 18 .…”
Section: Discussionmentioning
confidence: 99%
“…There appear to be multiple binding sequences across the primary sequences of all the sHsps, both in the ACD and in the N-and C-terminal regions (Ghosh et al 2007). Indeed, deletion of the Nterminal region does not prevent sHsps from binding to actin (Guo and Cooper 2000) or to tubulin and from chaperoning microtubules (Ohto-Fujita et al 2007). Whilst there is evidence that sequences from the Nterminal region and the ACD of both Hsp27 and αBc are effective inhibitors of actin assembly in vitro (Wieske et al 2001), the topic is contentious since Hsp27 mutants can stimulate actin polymerisation (Butt et al 2001) whereas another study using wild-type Hsp27 reported little to no significant change (Graceffa 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, previous papers showed that 'B-crystallin works as a molecular chaperone for actin (Singh et al 2007), and IFs (Nicholl and Quinlan 1994;Houck et al 2011). We showed that 'B-crystallin prevents tubulin aggregation in vitro (Arai and Atomi 1997;Ohto-Fujita et al 2007) and contributes to MT stability in 'B-crystallin overexpressing cultured cells (unpublished data). 'B-crystallin can function as a chaperone for the maintenance of cytoskeleton molecules.…”
Section: Adaptive Responses To Mechanical Stress: Stress Protein 'B-cmentioning
confidence: 70%
“…The protein turnover rate is higher in slow muscles due to higher rates of protein synthesis (Atomi et al 1991b) and higher chaperone contents have also been reported in slow muscle (Atomi et al 2000). 'B-crystallin is one of these chaperone proteins (Fujita et al 2004;Ohto-Fujita et al 2007) that is reported to be rich in the soleus muscle (Atomi et al 1991b;Koh and Escobedo 2004;Sakurai et al 2005). …”
Section: Two Types Of Muscle-related Force Energy and Adaptabilitymentioning
confidence: 98%